Ed Muskie, Political Parties, and the Art of Governance - Nicoll, Don (Maine Policy Review, 2020)
In its 200-year history as a state, Maine has gone through three major political realignments and is now in the midst of a fourth. The Jefferson Democratic Republicans supplanted the Federalists to achieve statehood. The Republican Party dominated state politics from the eve of the Civil War until 1954. The Maine Democratic Party, under the leadership of Edmund S. Muskie and Frank Coffin, transformed it into a competitive two-party state. Now the goals of open, responsive, and responsible governance that Muskie and Coffin sought through healthy competition and civil discourse are threatened by bitter, dysfunctional national trends in the political arena, threats now compounded by the COVID-19 pandemic and national revulsion over racial discrimination triggered by police violence against Black Americans. Could Maine play a role in restoring balance and correcting the ills that beset us?
Keywords: Maine Republican Party; Maine Democratic Party